Syntheses, X-ray structures, catalytic activity and magnetic properties of two new coordination polymers of Co(II) and Ni(II) based on benzenedicarboxylate and linear N,N `-donor Schiff base linkers - Bhattacharya, Biswajit; Maity, Dilip Kumar; Pachfule, Pradip; Colacio, Enrique; Ghoshal, Debajyoti (Inorganic Chemistry Frontiers, 2014)
{Two isostructural coordination polymers based on Co(II) and Ni(II), {[M(azpy)(3)(p-bdc)(2)(H2O)(4)]center dot(CH3OH)(2)(H2O)(3)}(n) [where M = Co (1) and Ni (2); azpy = N,N'-bis-pyridin-4-ylmethylene-hydrazine and p-bdc = 1,4-benzenedicarboxylate], have been synthesized using mixed ligand systems at room temperature and characterized by single-crystal X-ray diffraction and other physicochemical methods. Structure determination reveals that both the complexes crystallize in the monoclinic space group C2/c and exhibit one-dimensional (1D) ladder like structures constructed by p-bdc and azpy ligands in which Schiff base (azpy) linkers serve as a bridging as well as pendent ligands. These pendent ligands are involved in H-bonding and pi-pi interactions with lattice water, methanol molecules and bridging azpy ligands, to form the 3D supramolecular structure. Notably, both the frameworks efficiently catalyze the Knoevenagel condensation reactions of a wide range of substituted benzaldehydes with active methylene compounds in heterogeneous medium under environmentally friendly conditions and the products were obtained in excellent yields. These catalysts were also found to exhibit excellent recyclability and re-usability without any significant loss of activity. A variable temperature magnetic study of both compounds was carried out and their magnetic properties justified on the basis of their crystal structure.